1995
DOI: 10.1056/nejm199507203330303
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Infections Traced to Contamination of an Intravenous Anesthetic, Propofol

Abstract: With the increasing use of lipid-based medications, which support rapid bacterial growth at room temperature, strict aseptic techniques are essential during the handling of these agents to prevent extrinsic contamination and dangerous infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
1
15

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(239 citation statements)
references
References 34 publications
2
221
1
15
Order By: Relevance
“…ERIOPERATIVE infectious complications have been attributed to propofol as a possible causative agent [1][2][3][4] because of suspected lapses in aseptic technique when handling the drug. 1,5 The absence of preservatives in the propofol preparation may support microbial growth.…”
Section: [Le Maniement D'usage Du Propofol Prévient La Contamination mentioning
confidence: 99%
See 1 more Smart Citation
“…ERIOPERATIVE infectious complications have been attributed to propofol as a possible causative agent [1][2][3][4] because of suspected lapses in aseptic technique when handling the drug. 1,5 The absence of preservatives in the propofol preparation may support microbial growth.…”
Section: [Le Maniement D'usage Du Propofol Prévient La Contamination mentioning
confidence: 99%
“…1,5 The absence of preservatives in the propofol preparation may support microbial growth. [6][7][8][9][10][11][12][13][14] Admixture of thiopentone, 15 lidocaine [16][17][18][19] or disodium edetate 20 diminishes microbial growth in propofol, although microbial destruction is not achieved.…”
Section: [Le Maniement D'usage Du Propofol Prévient La Contamination mentioning
confidence: 99%
“…Although this was a case-control study on postoperative infections, 6 of the 7 outbreaks reported were associated only with receipt of propofol (ie, infusions or maintenance), and in only 1 of these 6 outbreaks was the microorganism (identical to that isolated from the patient) recovered from an opened vial of propofol. 3 Moreover, in the same article, Bennett et al reported 2 deaths that Vonberg and Gastmeier also probably missed. Perhaps the web database (an unofficial platform of outbreaks) 2 selected by the authors was not appropriate to correctly answer the question posed in the review.…”
Section: Inconsistencies Regarding the Number Of Outbreaks And Mortalmentioning
confidence: 96%
“…2 Recently, outbreaks in the United States, Turkey, and some European countries have led to the recognition of tularemia as an emerging infectious disease. 3 F. tularensis is a highly infectious agent; a quantity of just 10-25 bacteria can infect a human and cause severe clinical disease. Hence, F. tularensis is considered a 'category A' bioterrorism agent.…”
Section: Potential Risk Of Aerosol-borne Francisella Tularensis Transmentioning
confidence: 99%
“…Single source outbreaks of Enterobacter infections have been frequently traced to contaminated intravenous products, blood products, distilled water and pressure monitoring devices 2,7,22,24,25,31,32,34,35 . A longlasting epidemic caused by Enterobacter spp involving many hospitals and associated with the use of intrinsically contaminated intravenous solutions was reported in the 1970's in the United States by MAKI et al 22 .…”
Section: Introductionmentioning
confidence: 99%